Financial innovation and endogenous growth - Laeven, Luc; Levine, Ross; Michalopoulos, Stelios (Journal of Financial Intermediation, 2015)
Is financial innovation necessary for sustaining economic growth? To address this question, we build a Schumpeterian model in which entrepreneurs earn profits by inventing better goods and profit-maximizing financiers arise to screen entrepreneurs. The model has two novel features. First, financiers engage in the costly but potentially profitable process of innovation: they can invent better methods for screening entrepreneurs. Second, every screening process becomes less effective as technology advances. The model predicts that technological innovation and economic growth eventually stop unless financiers innovate. Empirical evidence is consistent with this dynamic, synergistic model of financial and technological innovation.